Balance of payment and import substitution in Nigeria - Oshiyoye, Adebayo Olukayode (Washington, D.C.: Howard University, 1975)
The thesis analyzes, evaluates the main features of the process of import substitution within the context of Nigerian experience.
A dissertation submitted to the Faculty of Graduate School of Howard University in partial fulfillment of the requirements for the degree of master of arts.
Includes bibliographical references.
oif 15/04/2019
Thesis
Keywords: Balance of payments; Economics; Imports; Nigeria